Effect ofBacillus velezensis JC-K3 on Endophytic Bacterial and Fungal Diversity in Wheat Under Salt Stress - Ji, Chao; Wang, Xiaohui; Song, Xin; Zhou, Qisheng; Li, Chaohui; Chen, Zhizhang; Gao, Qixiong; Li, Huying; Li, Jintai; Zhang, Pengcheng; Cao, Hui (Frontiers in Microbiology, 2021)
Plant growth-promoting bacteria (PGPB) can effectively reduce salt damage in plants. Currently, there are many studies on the effects of PGPB on the microbial community structure of rhizosphere soil under salt stress, but fewer studies on the community structure of endophytic bacteria and fungi. We propose that inoculation of endophytic bacteria into the rhizosphere of plants can significantly affect the microbial community structure of the plant’s above-ground and underground parts, which may be the cause of the plant’s “Induced Systemic Tolerance.” The isolated endophytes were re-inoculated into the rhizosphere under salinity stress. We found that, compared with the control group, inoculation with endophytic Bacillus velezensis JC-K3 not only increased the accumulation of wheat biomass, but also increased the content of soluble sugar and chlorophyll in wheat, and reduced the absorption of Na in wheat shoots and leaves. The abundance of bacterial communities in shoots and leaves increased and the abundance of fungal communities decreased after inoculation with JC-K3. The fungal community richness of wheat rhizosphere soil was significantly increased. The diversity of bacterial communities in shoots and leaves increased, and the richness of fungal communities decreased. JC-K3 strain improved wheat’s biomass accumulation ability, osmotic adjustment ability, and ion selective absorption ability. In addition, JC-K3 significantly altered the diversity and abundance of endophytic and rhizosphere microorganisms in wheat. PGPB can effectively reduce plant salt damage. At present, there are many studies on the effect of PGPB on the microbial community structure in rhizosphere soil under salt stress, but there are few studies on the community structure changes of endophytic bacteria and fungi in plants.